Understanding of Accounting, Student Activeness, Learning Behavior and Department Background, On Ability to Prepare Financial Reports - Nur Inayah; Kintan Eryka Fitri; Sartono Sartono (Islamic Accounting Journal, 2022)
The purpose of this study is to determine the understanding of accounting, student activity, background majors, and learning behavior towards the ability to compile financial reports for student. This study used a quantitative descriptive analysis method with a research instrument in the form of a questionnaire distributed onlie with the help of google form. The sample used in this study was 75 students majoring in Islamic accounting class 2018 IAIN Salatiga. Data analysis using Multiple Linear Regression analysis. The results showed that accounting understanding and learning behavior had a significant effect on the ability to compile financial reports, while student activeness and background majors had no significant effect on the ability to compile financial reports.Keywords: accounting understanding,, student activeness, department background, learning behavior, financial reports.Keywords: accounting understanding,, student activeness, department background, learning behavior, financial reports.